Investasi Berkelanjutan Peran INA (Indonesia Investment Authority) dalam Optimalisasi Kerangka ESG (Environment, Social and Governance) - Sukarsa, Galuh; Akhmadi, Muhammad Heru (Politeknik Piksi Ganesha Indonesia, 2024)
Infrastructure development stands as a main focus for the government in achieving Indonesia Emas 2045. Referring to the expansive State Budget, it urges the government to optimize the investment funding of the Sovereign Wealth Fund (SWF), known as the Indonesia Investment Authority (INA). INA is aimed at aligning infrastructure development with the enhancement of environmental, social, and governance (ESG) standards. The research utilized a literature review to examine the development of ESG integration within INA and its implementation in different countries. The findings indicate that INA has begun incorporating ESG principles in its investment activities, as highlighted in the 2022 INA Annual Report. Nevertheless, there is a need for INA to further refine its ESG practices, drawing inspiration from the regulatory frameworks and corporate collaborations seen in China and Norway. To this end, INA is anticipated to advance its ESG efforts by focusing on environmental, social, and governance metrics